Where is the Limit? Barriers of Theories – Organisations without Boundaries - Szintay, István (Theory, Methodology, Practice – Review of Business and Management, 2012)
The paper addresses the issue of inter-organisational cooperation. Networks change economic relations fundamentally; however, theory has devoted so far relatively little attention to this development of significance in economic history. It can be attributed to the fact that many evaluate the transformation of large vertical concerns into loose networks as unambiguously as gaining ground by the market against hierarchies. Although there is no doubt that the transformation of large organisations into networks of independent contractors revitalises the market, at the same time it also changes the nature of market relations.